Super-early-strength and high-strength support grouting material and preparation method thereof
By using sulfaluminate cement, silica fume and quartz sand and adding appropriate amount of auxiliary agents, super early strength high strength support grouting material was prepared, which solved the problems of unstable strength and low early strength in the existing technology, and achieved high strength, fast hardness and durability.
Patent Information
- Application Number
- CN202510117690.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-15
AI Technical Summary
The existing super early strength high-strength bearing grout materials have problems such as unstable strength, low early strength, less strength growth in the later stage, water leakage, gray cracking on the surface after solidification, and poor adhesion of the grout materials to the base layer of the bearing.
Sulfur aluminate cement and silica fume are used as cementitious materials, supplemented with quartz sand to improve fluidity and filling properties, and early strength agent, water reducer, expansion agent, thickener, defoamer and retarder are added to prepare ultra-premature strength high strength support grouting material through specific proportioning and mixing processes.
It achieves high strength, fast hardness, no shrinkage, good durability, convenient construction and environmental protection performance, overcomes the problems in the existing technology, is easy to use, has low glue usage and low overall cost.
Smart Images

Figure CN119822764A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building material grouting materials, and in particular to an ultra-early-strength high-strength bearing grouting material and a preparation method thereof. Background Art
[0002] Building material grouting material is a kind of building cementitious material with the characteristics of no shrinkage, low expansion, high early strength and no shrinkage in late strength, good fluidity, no water seepage and good cohesion. It is often used for high-strength grouting and repair, and can also be used for engineering structure reinforcement, equipment installation, prefabricated buildings, etc. Hardened cement-based grouting material can provide good durability and strength without causing pollution. Cement-based high-performance grouting material is mainly composed of high-specific surface area sulphoaluminum cement, various admixtures, graded aggregates and compatible admixtures, which can achieve ultra-high fluidity and ultra-high strength at low water-cement ratio. The raw materials of high-performance grouting material can reach more than a dozen. Appropriate admixtures need to be used in the compounding process to meet the performance requirements of initial and late strength of fluidity, flexural strength, expansion rate and water seepage rate.
[0003] Super-early-strength high-strength grouting materials have been widely used in various projects due to their performance advantages such as super-early strength, high strength, no shrinkage, fast hardening, good durability, convenient construction and environmental protection. As a special grouting material for bearings, super-early-strength high-strength bearing grouting materials can withstand large loads in a short time, and are particularly suitable for foundation grouting of heavy equipment and bridges. At the same time, the non-shrinkage characteristics ensure the density and uniformity of the grouting layer, avoid shrinkage cracking, and improve the safety and durability of the project. The material has the characteristics of rapid hardening, can reach the design strength in a short time, and significantly shortens the construction period. For example, the strength can reach more than 50MPa within one day, and it can be put into operation and production after pouring, which greatly improves the construction efficiency. It can be seen that super-early-strength high-strength bearing grouting materials not only improve the quality of the project, but also shorten the construction period, reduce the construction cost, and bring profound changes to the construction industry. In the future, with the continuous advancement of science and technology and the continuous development of the construction industry, super-early-strength high-strength grouting materials will surely play an important role in more fields.
[0004] However, the existing ultra-early strength and high-strength bearing grouting materials generally have problems such as unstable strength, low early strength, small increase in later strength, water seepage of the grouting material, dusting and cracking on the surface after solidification, and poor adhesion between the grouting material and the bearing base. Summary of the invention
[0005] In view of the above problems, the present invention proposes an ultra-early-strength high-strength bearing grouting material and a manufacturing method thereof.
[0006] The ultra-early-strength high-strength bearing grouting material of the present invention uses sulphoaluminate cement and silica fume as cementing materials, supplemented with quartz sand to improve its fluidity and filling properties; and comprises the following components in weight percentage:
[0007]
[0008]
[0009] Preferably, the ultra-early-strength high-strength bearing grouting material comprises the following components in percentage by weight:
[0010]
[0011] Preferably, the sulphoaluminate cement is a raw material of limestone: alumina: gypsum = 10-13: 3-5: 0.6-1, calcined at 1300-1350°C to produce a clinker with anhydrous calcium sulphoaluminate C4A3S and dicalcium silicate C2S as main mineral components, and then mixed with a composition of dihydrate gypsum: silica fume = 1-2: 1.6-2 and ground together;
[0012] The silica fume is the dust collected and treated by the capture device during the high-temperature smelting of industrial silicon and ferrosilicon with the exhaust gas. The SiO2 content accounts for more than 90% of the total dust, and the average particle size is nanometer level. The amount of silica fume added accounts for 4-6% of the total grouting material.
[0013] The quartz sand is quartz particles made by crushing white quartzite, and its silicon dioxide content is not less than 99.6%, and the grading ratio is: 10% for 10-20 mesh, 60% for 20-40 mesh, and 30% for 40-80 mesh.
[0014] Preferably, the early strength agent is a nanocrystalline core early strength agent, that is, a nanocrystalline core early strength agent containing nano-particle-size calcium silicate hydrate.
[0015] Preferably, the water reducer includes lignin common water reducer, naphthalenesulfonate water reducer, aliphatic water reducer, aminosulfonate water reducer and polycarboxylate water reducer.
[0016] Preferably, the expansion agent is plastic expansion agent EP-2, which is made of bauxite mineral as the main material, sintered at 1700° C. in a nitrogen atmosphere in the presence of carbon and calcium oxide, and then surface treated and ground into yellow powder.
[0017] Preferably, the thickener is a mixture of hydroxypropyl methylcellulose and starch ether with a viscosity of ≤400 Pa·S, and the mixing ratio is 2:1.
[0018] Preferably, the defoamer is a polyether alcohol ester powdered defoamer, that is, a modified polysiloxane high-efficiency defoamer.
[0019] Preferably, the retarder is boric acid.
[0020] The method for preparing the ultra-early-strength high-strength bearing grouting material of the present invention comprises the following steps:
[0021] S1. Weigh the raw and auxiliary materials according to the required proportions and set aside;
[0022] S2. Mix the auxiliary materials, mix the early strength agent, water reducing agent, expansion agent, thickener, defoamer and retarder evenly, and set aside;
[0023] S3, mixing the main materials, mixing sulphoaluminate cement and quartz sand evenly;
[0024] S4, add the mixed auxiliary materials to the mixed main materials, and continue mixing until completely uniform;
[0025] S5, sieving to obtain the powder of the ultra-early strength high-strength bearing grouting material;
[0026] S6. Preparation of slurry: According to the volume of bearing to be grouted, weigh 1.2 times the volume of dry powder grouting material, calculate the water consumption according to the water-to-material ratio of 0.13 to 0.15:1, mix the water and dry powder grouting material and stir rapidly for 2 to 3 minutes to obtain the slurry of ultra-early strength and high-strength bearing grouting material.
[0027] The beneficial technical effect of the ultra-early-strength high-strength bearing grouting material and the preparation method thereof of the present invention is that the problems existing in the bearing grouting materials of the prior art are overcome, and the material usage is low and the overall cost is low, which is convenient to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Attached Figure 1 The present invention is a process flow chart of the method for producing the ultra-early strength and high-strength bearing grouting material.
[0029] The ultra-early-strength high-strength bearing grouting material and its production method of the present invention are further described below in conjunction with the accompanying drawings and specific implementation methods. DETAILED DESCRIPTION
[0030] The ultra-early-strength high-strength bearing grouting material of the present invention uses sulphoaluminate cement and silica fume as cementing materials, supplemented with quartz sand to improve its fluidity and filling properties; and comprises the following components in weight percentage:
[0031]
[0032]
[0033] As one of the preferred solutions, the ultra-early-strength high-strength bearing grouting material comprises the following components in weight percentage:
[0034]
[0035] The ultra-early-strength high-strength bearing grouting material of the present invention uses sulphoaluminate cement and silica fume as cementitious materials, supplemented by quartz sand to improve its fluidity and filling properties; coupled with the combined effect of other auxiliary agents, the ultra-early-strength high-strength bearing grouting material of the present invention ensures high strength while ensuring its ultra-early setting strength and high fluidity, high self-compactness and filling properties, can be directly poured into the equipment foundation, can automatically fill all gaps in the equipment foundation without vibration, and can ensure the uniformity and density of grouting, effectively improving the construction quality. Especially when dealing with complex structures and narrow spaces, its superiority is particularly prominent.
[0036] As one of the preferred technical solutions, the sulphoaluminate cement is a clinker composed of anhydrous calcium sulphoaluminate C4A3S and dicalcium silicate C2S as main minerals, which is calcined at 1300-1350°C with a composition of limestone: alumina: gypsum = 10-13: 3-5: 0.6-1 as raw materials, and then mixed with a composition of dihydrate gypsum: silica fume = 1-2: 1.6-2 and ground together; the silica fume refers to the dust collected and treated by a capture device during the high-temperature smelting of industrial silicon and ferrosilicon with the smoke escaping from the exhaust gas, the SiO2 content accounts for more than 90% of the total dust, and the average particle size is nanometer level; the amount of the added silica fume accounts for 4-6% of the total amount of the grouting material; the quartz sand is quartz particles made by crushing white quartzite, the silicon dioxide content of which is not less than 99.6%, and the grading ratio is: 10% for 10-20 mesh, 60% for 20-40 mesh, and 30% for 40-80 mesh. The sulphoaluminate cement prepared according to the above method has a series of excellent properties such as early strength, fast hardening and low alkalinity; the particle size of silica fume is very small, the average particle size is nanometer level, and the particle size is reasonable. After mixing with sulphoaluminate cement, it can reduce and eliminate the stratification and water seepage of grouting materials; it can enhance the tensile and compressive strength of the solidified material, improve the wear resistance, and increase the durability of the grouting material such as crack resistance and impermeability; quartz sand is quartz particles processed by crushing white quartzite, and its main component is silicon dioxide, which has the characteristics of high hardness, wear resistance and good chemical stability. In terms of physical properties, quartz sand is milky white or colorless and translucent, with a Mohs hardness of 7, high hardness and wear resistance, rounded particles, and high solid area ratio. Adding quartz sand can make the cementitious material have excellent fluidity and filling properties.
[0037] As one of the preferred embodiments, the early strength agent is a nanocrystalline core early strength agent, i.e., a nanocrystalline core early strength agent containing nano-particle size calcium silicate hydrate. The nanocrystalline core early strength agent can effectively promote the hydration process of early cement (6-12 hours); based on its unique and innovative seed crystal technology, the growth of calcium silicate hydrate crystals in cement slurry is accelerated, and the hardening of cement can be promoted at low temperatures and thermal curing temperatures. Different from traditional early strength agents, the crystal nucleus can grow unimpeded between cement particles, the early strength develops rapidly, and the later strength is not affected.
[0038] As one of the preferred solutions, the water reducer includes lignin common water reducer, naphthalenesulfonate water reducer, aliphatic water reducer, aminosulfonate water reducer and polycarboxylate water reducer. Among them, after the polycarboxylate water reducer is adsorbed on the surface of cement particles, it uses electrostatic repulsion or steric hindrance effect to divide cement particles and maintain the fluidity of the slurry. The structure of the polycarboxylate water reducer has both hydrophobic and hydrophilic components. By forming an adsorption film on the surface of cement particles, the charge state of cement particles is changed, so that the cement-based materials quickly repel each other during the stirring process, thereby dispersing cement particles, reducing agglomeration, and improving the fluidity of the grouting material. Because the polycarboxylate water reducer can make the grouting material have high fluidity and high self-compactness, it can be directly poured into the equipment foundation, and can automatically fill all the gaps in the equipment foundation without vibration, thereby improving the construction quality. It can be seen that the polycarboxylate water reducer has a higher water reduction rate and better fluidity and durability.
[0039] As one of the preferred solutions, the expansion agent is a plastic expansion agent EP-2, which is made of bauxite mineral as the main material, sintered at 1700°C in a nitrogen atmosphere in the presence of carbon and calcium oxide, and then surface treated and ground into a yellow powder. The expansion agent is mainly used to compensate for the volume shrinkage of concrete during the hardening process. It can produce tiny bubbles in the concrete, thereby producing an expansion effect during the hardening process. These bubbles can not only effectively compensate for the shrinkage of concrete, but also improve the crack resistance and durability of concrete. The expansion agent is usually a yellow powder with good hydrolysis resistance and environmental protection performance. Its main properties include low dosage, uniform and dense pores, obvious early expansion and long duration.
[0040] As one of the preferred solutions, the thickener is a mixture of hydroxypropyl methylcellulose and starch ether with a viscosity of ≤400 Pa·S, and the mixing ratio is 2:1. The thickener can significantly improve the cohesiveness and water retention of the grouting material, and prevent the grouting material from bleeding and stratification. The use of a mixture of hydroxypropyl methylcellulose and starch ether as a thickener can increase the adhesion between the grouting material and the base layer while ensuring the fluidity of the grouting material, thereby improving the fluidity and later strength of the grouting material.
[0041] As one of the preferred solutions, the defoamer is a polyether alcohol ester powdered defoamer, i.e. a modified polysiloxane high-efficiency defoamer. The defoamer is mainly designed for the foaming characteristics during the mixing process of the grouting material, has good diffusivity and permeability, can effectively control the foam generation in the cement mortar system, and make the concrete components more dense, bright and stronger.
[0042] As one of the preferred solutions, the retarder is boric acid. The retarder can appropriately delay the setting time of sulphoaluminium cement, so as to facilitate the preparation and pouring construction of grouting material.
[0043] The method for preparing the ultra-early-strength high-strength bearing grouting material of the present invention comprises the following steps:
[0044] S1. Weigh the raw and auxiliary materials according to the required proportions and set aside;
[0045] S2. Mix the auxiliary materials, mix the early strength agent, water reducing agent, expansion agent, thickener, defoamer and retarder evenly, and set aside;
[0046] S3, mixing the main materials, mixing sulphoaluminate cement and quartz sand evenly;
[0047] S4, add the mixed auxiliary materials to the mixed main materials, and continue mixing until completely uniform;
[0048] S5, sieving to obtain the powder of the ultra-early strength high-strength bearing grouting material;
[0049] S6. Preparation of slurry: According to the volume of bearing to be grouted, weigh 1.2 times the volume of dry powder grouting material, calculate the water consumption according to the water-to-material ratio of 0.13 to 0.15:1, mix the water and dry powder grouting material and stir rapidly for 2 to 3 minutes to obtain the slurry of ultra-early strength and high-strength bearing grouting material.
[0050] From the above production process, it can be seen that the ultra-early strength and high-strength bearing grouting material of the present invention only needs to add a small amount of water for mixing to prepare the slurry, and the mixing time of the slurry and the pouring time of the construction need to be strictly controlled to ensure the construction quality.
[0051] In order to verify the various performances and indicators of the ultra-early-strength high-strength bearing grouting material of the present invention, the ultra-early-strength high-strength bearing grouting material of the present invention is tested according to the standards of GB50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials" and JT / T1130-2017 "Bridge Bearing Grouting Materials". The specific embodiments are as follows:
[0052] 1. Embodiment 1
[0053] Preparation of the ultra-early-strength high-strength bearing grouting material of the present invention:
[0054] (1) Various raw and auxiliary materials are accurately measured and prepared according to the ratio requirements, among which the main materials are: 45% sulphoaluminate cement, 5% silica fume, and 49.54% quartz sand; the grading of quartz sand is: 10-20 mesh 10.09%, 20-40 mesh 60.56%, and 40-80 mesh 29.35%; auxiliary materials: 0.2% nanocrystalline core early strength agent, 0.06% polycarboxylic acid water reducer, 0.05% EP-2 plastic expansion agent, 0.04% hydroxypropyl methylcellulose, 0.02% starch ether, 0.04% modified polysiloxane high-efficiency defoaming agent, and 0.05% boric acid.
[0055] (2) Mix the auxiliary materials. Put the crystal nucleus early strength agent, water reducing agent, swelling agent, hydroxypropyl methylcellulose, starch ether, defoaming agent and boric acid into a small mixer and mix for 3-5 minutes. Put them into a special small bucket for later use.
[0056] (3) Mix the main ingredients: put sulphoaluminate cement, silica fume and quartz sand into a large mixer and mix for 3-5 minutes for later use;
[0057] (4) Preparation of powder: put the mixed auxiliary materials into a large mixer and mix them with the mixed main materials for 5-8 minutes. After mixing evenly, bag them to obtain the ultra-early strength high-strength bearing grouting material powder;
[0058] (5) Preparation of slurry: Calculate the amount of water according to the water-to-cement ratio of 0.14:1, and quickly mix water and grouting material powder for 2-3 minutes to obtain the slurry of ultra-early strength high-strength bearing grouting material;
[0059] (6) Grouting: Use gravity grouting to grout the bearings. Pour the prepared bearing grouting material at the bottom of the bearing. The grouting time is 5-20 minutes. Strictly control the positioning and slurry elevation. Cover or apply a film to keep it moist within 30 minutes after grouting and maintain for 3-7 days.
[0060] 2. Embodiments 2 to 5
[0061] The preparation methods and steps of Examples 2 to 5 are exactly the same as those of Example 1, except that the usage and / or amount of auxiliary materials are adjusted, and the total amount of raw and auxiliary materials is the same as that of Example 1 by increasing or decreasing the amount of 40-80 mesh quartz sand added. See Table 1 below for details.
[0062] Table 1: Composition ratio of Examples 1 to 5
[0063]
[0064] According to the requirements of GB50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials" and JT / T1130-2017 "Grouting Materials for Bridge Supports", various indicators of Examples 1 to 5 were tested and compared with the performance standard values of early strength type I in JT / T1130-2017 "Grouting Materials for Bridge Supports". The results are shown in Table 2 below:
[0065] Table 2: Comparison of performance indicators of bridge bearing grouting materials
[0066]
[0067]
[0068] 3. Results Analysis
[0069] In Examples 1 and 2, using only hydroxypropyl methylcellulose as the thickener has a significant impact on the fluidity and 1-day and 28-day strength of the bearing grouting material. Using all hydroxypropyl methylcellulose as the thickener reduces the fluidity of the bearing grouting material and also reduces the 1-day and 28-day strength. Using some starch ether can not only increase the adhesion between the grouting material and the base layer, but also improve the fluidity and later strength of the grouting material.
[0070] In Examples 1, 3, and 4, reducing the amount of the nanocrystalline core early strength agent reduces the 2h and 1-day strength of the grouting material, and slightly increases the setting time, but the strength at 28 days in the later period increases. Adding the nanocrystalline core early strength agent significantly improves the 2h and 1-day strength of the grouting material, shortens the setting time, but the strength at 28 days in the later period decreases.
[0071] In Examples 1 and 5, the retarder boric acid has a significant retarding effect on the sulphoaluminate cement; when no boric acid is added, the setting time of the grouting material is significantly shortened, and the fluidity is also reduced, especially after 30 minutes, the fluidity decreases rapidly.
[0072] In summary, the component ratio of Example 1 should be relatively reasonable, and all indicators can meet the requirements of the early strength type I performance standard value of JT / T1130-2017 "Bridge Bearing Grouting Materials", and it has the performance advantages of fast hardening, super early strength, high strength, high flexural resistance, good base adhesion, no shrinkage, good durability, convenient construction and environmental protection.
[0073] Obviously, the beneficial technical effect of the ultra-early-strength high-strength bearing grouting material and the preparation method thereof of the present invention is that it overcomes the problems existing in the bearing grouting materials of the prior art, and is easy to use, has a low amount of adhesive material and a low overall cost.
Claims
1. An ultra-early-strength high-strength bearing grouting material, characterized in that: Sulphoaluminate cement and silica fume are used as cementitious materials, supplemented with quartz sand to improve its fluidity and filling properties; The composition includes the following weight percentages:
2. The ultra-early-strength high-strength bearing grouting material according to claim 1 is characterized in that: The ultra-early-strength high-strength bearing grouting material comprises the following components in percentage by weight:
3. The ultra-early-strength high-strength bearing grouting material according to claim 1 or 2, characterized in that: The sulphoaluminate cement is prepared by using a composition of limestone: alumina: gypsum = 10-13: 3-5: 0.6-1 as raw materials, calcined at 1300-1350° C. to produce a clinker with anhydrous calcium sulphoaluminate C4A3S and dicalcium silicate C2S as main mineral components, and then adding a composition of dihydrate gypsum: silica fume = 1-2: 1.6-2 and grinding together; The silica fume is the dust collected and treated by the capture device during the high-temperature smelting of industrial silicon and ferrosilicon with the exhaust gas. The SiO2 content accounts for more than 90% of the total dust, and the average particle size is nanometer level. The amount of silica fume added accounts for 4-6% of the total grouting material. The quartz sand is quartz particles made by crushing white quartzite, and its silicon dioxide content is not less than 99.6%, and the grading ratio is: 10% for 10-20 mesh, 60% for 20-40 mesh, and 30% for 40-80 mesh.
4. The ultra-early-strength high-strength bearing grouting material according to claim 1 or 2, characterized in that: The early strength agent is a nano-crystal core early strength agent, that is, a nano-crystal core early strength agent containing nano-particle-size hydrated calcium silicate.
5. The ultra-early-strength high-strength bearing grouting material according to claim 1 or 2, characterized in that: The water reducer includes lignin common water reducer, naphthalenesulfonate water reducer, aliphatic water reducer, aminosulfonate water reducer and polycarboxylate water reducer.
6. The ultra-early-strength high-strength bearing grouting material according to claim 1 or 2, characterized in that: The expansion agent is plastic expansion agent EP-2, which is made of bauxite mineral as the main material, sintered at 1700°C in a nitrogen atmosphere in the presence of carbon and calcium oxide, and then surface treated and ground into yellow powder.
7. The ultra-early-strength high-strength bearing grouting material according to claim 1 or 2, characterized in that: The thickener is a mixture of hydroxypropyl methylcellulose and starch ether with a viscosity of ≤400 Pa·S, and the mixing ratio is 2:
1.
8. The ultra-early-strength high-strength bearing grouting material according to claim 1 or 2, characterized in that: The defoamer is a polyether alcohol ester powdered defoamer, that is, a modified polysiloxane high-efficiency defoamer.
9. The ultra-early-strength high-strength bearing grouting material according to claim 1 or 2, characterized in that: The retarder is boric acid.
10. A method for preparing the ultra-early-strength high-strength bearing grouting material of the present invention, characterized in that: The grouting material is prepared by using any one of the grouting material components of claims 1 to 9, comprising the following steps: S1. Weigh the raw and auxiliary materials according to the required proportions and set aside; S2. Mix the auxiliary materials, mix the early strength agent, water reducing agent, expansion agent, thickener, defoamer and retarder evenly, and set aside; S3, mixing the main materials, mixing sulphoaluminate cement and quartz sand evenly; S4, add the mixed auxiliary materials to the mixed main materials, and continue mixing until completely uniform; S5, sieving to obtain the powder of the ultra-early strength high-strength bearing grouting material; S6. Preparation of slurry: According to the volume of bearing to be grouted, weigh 1.2 times the volume of dry powder grouting material, calculate the water consumption according to the water-to-material ratio of 0.13 to 0.15:1, mix the water and dry powder grouting material and stir rapidly for 2 to 3 minutes to obtain the slurry of ultra-early strength and high-strength bearing grouting material.